The Role of Accounting Information in Strategic Management - Sharma, Dr.Ravinder; Maurya, Dr. Shyam (International Journal of Accounting and Economics Studies, 2025)
The steps in the strategic management process (SMP) are mission definition, goal-setting, strategy formulation, strategic plan implementation, and plan evaluation. In order to analyze negative deviations from goals and to examine the entire process in order to optimize objectives, the evaluation step of SMP is an accounting function that necessitates a complex financial data information system. A vital component of modern life, accounting data serves as the foundation for strategic decision-making and is required to comprehend the precise financial status of the company. Since strategic choices have a lasting impact on the company, it is crucial to examine accounting data while making long-term strategic choices. The goal of the current study is to assess how decision makers use accounting data in strategic decision-making processes. The study took into consideration five strategic choice areas: marketing, manufacturing, human resources, long-term investment, and basic strategic decisions.
Keywords: Accounting Information; Strategic Decision; Manufacturing Industries; Bangladesh